Electrocatalyst nanoparticles go with the flow - Peljo Pekka; Kallio Tanja (Springer Nature, 2022)
Electric current is now shown to induce movement of the atoms in electrocatalyst nanoparticles, leading to morphological changes and performance degradation. This electromigration effect needs to be taken into account when designing nanostructured catalysts for electrochemical devices.